Defectiveness of external and internal surfaces of the main oil and gas pipelines after long-term operation - Maruschak, Pavlo; Prentkovskis, Olegas; Bishchak, Roman (Journal of Civil Engineering and Management, 2016)
Damage by pitting corrosion of the surface areas of the local oil and gas pipelines was identified and numeri-cally analysed in this paper. Having used the methods of optical and scanning electron microscopy, the basic laws of structural and mechanical degradation were established. Based on the data of fractographic control, the shape of defects and substantiated morphological characteristics were examined. It was established that certain informative signs of the defects correspond to certain stages of operation. Having used methods of fractodiagnostics, the main reasons for the performance defects of main oil and gas pipelines were established, and the mechanisms of degradation as well as frac-ture of the materials they are made from were described. According to the findings, the cause of the decrease in the reli-ability of the main oil and gas pipeline networks is general and localised corrosion as well as technological defects in the pipeline metal. These studies are essential for the establishment of the complex of mechanical and corrosion-mechanical properties, particularly sensitive to degradation in the steel used for the pipe wall after a lengthy use of a pipe.